Method for brazing boron nitride ceramic to nickel-based superalloy
By using solder paste made from nickel-based amorphous powder and titanium hydride powder, combined with a Ti layer and controlled brazing process parameters, the problem of difficult bonding between boron nitride ceramics and nickel-based superalloys was solved, resulting in a high-strength joint suitable for thermal management in aerospace and nuclear energy fields.
Patent Information
- Application Number
- CN202511569648.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-30
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2045-10-30
Smart Images

Figure CN121377807B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of brazing heat treatment technology, and in particular to a brazing heat treatment method for boron nitride ceramics and nickel-based superalloys. Background Technology
[0002] Extreme working conditions in fields such as aerospace, nuclear fusion, and deep well drilling place high demands on materials. Traditional single materials are insufficient, requiring the combination of the high thermal conductivity, electrical insulation, and thermal shock resistance of ceramics with the high strength, creep resistance, and oxidation resistance of metals / alloys. In other words, effective bonding between ceramics and metals / alloys is necessary.
[0003] The high melting point and brittleness of ceramics make it impossible for traditional fusion welding and pressure welding to achieve an effective connection between the two. Although brazing uses filler metal with a lower melting point to effectively connect some ceramics (such as SiC and Si3N4) to metals through interfacial reaction, the inertness of boron nitride ceramics means that it will hardly have an interfacial reaction with the filler metal, making it difficult to achieve an effective connection between the two through brazing. Summary of the Invention
[0004] Based on the above analysis, the present invention aims to provide a brazing heat treatment method for boron nitride ceramics and nickel-based superalloys, in order to solve the problem that existing boron nitride ceramics and nickel-based superalloys cannot be effectively connected by brazing processes.
[0005] On one hand, embodiments of the present invention provide a brazing heat treatment method for boron nitride ceramics and nickel-based superalloys, the method comprising:
[0006] (1) Apply solder paste between the boron nitride ceramic and the nickel-based high-temperature alloy surfaces to be soldered;
[0007] (2) Mold clamping;
[0008] (3) The boron nitride ceramic and the nickel-based high-temperature alloy are brazed at a temperature of 1000℃-1100℃ for 5min-25min to achieve the brazing connection.
[0009] Furthermore, in step (1), the solder paste comprises nickel-based amorphous powder and titanium hydride powder.
[0010] Furthermore, the mass ratio of the nickel-based amorphous powder to the titanium hydride powder is 7:3 to 9:1.
[0011] Furthermore, the thickness of the solder paste is 50-200mm.
[0012] Furthermore, in step (1), a Ti layer is deposited on the surface of the boron nitride ceramic.
[0013] Furthermore, in step (2), the pressure of the mold clamping is 0.2-1 MPa.
[0014] Furthermore, in step (3), the brazing heat treatment also includes three stages: a heating stage and a cooling stage;
[0015] Furthermore, the vacuum degree of the brazing heat treatment is 3×10⁻⁶. -3 Pa ~ 5 × 10 -3 Pa.
[0016] Furthermore, the heating rate during the heating phase is 8°C / min to 12°C / min.
[0017] Furthermore, the cooling specifically includes: first reducing the temperature to 400-500°C at a rate of 2-6°C / min, and then furnace cooling to room temperature.
[0018] On the other hand, embodiments of the present invention also provide a connecting joint between boron nitride ceramic and nickel-based high-temperature alloy, wherein the connecting joint is prepared by the method described above, and the shear stress of the connecting joint is 0.4-4 MPa at 25°C.
[0019] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0020] 1. Compared with the prior art, the present invention achieves brazing connection between boron nitride ceramics and nickel-based superalloys by adjusting the process conditions of brazing heat treatment, including using mold clamping, and the temperature and time of brazing heat treatment.
[0021] 2. This invention regulates the composition and amount of brazing paste and coordinates the brazing heat treatment process conditions to achieve an effective connection between boron nitride ceramics and nickel-based superalloys.
[0022] 3. The present invention regulates the cooling process of the brazing heat treatment, which can prevent excessive concentration of thermal stress between dissimilar materials during the cooling stage after the brazing heat treatment is completed, thus preventing brazing connection failure.
[0023] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objects and other advantages of this invention can be realized and obtained from what is particularly pointed out in the description and drawings. Attached Figure Description
[0024] The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Throughout the drawings, the same reference numerals denote the same parts.
[0025] Figure 1 This is a schematic diagram of the process for the brazing heat treatment method of boron nitride ceramics and nickel-based superalloys according to the present invention.
[0026] Figure 2 A photograph of the connector prepared by the method of the present invention;
[0027] Figure 3 Here is a SEM image of the connector prepared by the method of the present invention;
[0028] Figure 4 This is a schematic diagram of the structure of the connector prepared by the method of the present invention;
[0029] Figure label:
[0030] 1-Ni-based superalloy; 2-Ni-based superalloy-brazing reactant layer; 3-Brazing solder layer; 4-Brazing solder-Ti reactant layer; 5-Ti layer; 6-Ti layer-boron nitride reactant layer; 7-BN ceramic. Detailed Implementation
[0031] The preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, which constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.
[0032] The high melting point and brittleness of ceramics make it impossible for traditional fusion welding and pressure welding to achieve an effective connection between the two. Although brazing uses filler metal with a lower melting point to effectively connect some ceramics (such as SiC and Si3N4) to metals through interfacial reaction, the inertness of boron nitride ceramics means that it will hardly have an interfacial reaction with the filler metal, making it difficult to achieve an effective connection between the two through brazing.
[0033] Therefore, the present invention provides a brazing heat treatment method for boron nitride ceramics and nickel-based superalloys, the method comprising:
[0034] (1) Apply solder paste between the boron nitride ceramic and the nickel-based high-temperature alloy surfaces to be soldered;
[0035] (2) Mold clamping;
[0036] (3) The boron nitride ceramic and the nickel-based high-temperature alloy are brazed at a temperature of 1000℃-1100℃ for 5min-25min to achieve the brazing connection.
[0037] It should be noted that, in order to enable the boron nitride ceramic and the brazing filler metal to undergo an interfacial reaction at the brazing heat treatment temperature and achieve an effective connection, the composition of the brazing paste needs to be limited in this invention.
[0038] Specifically, in step (1), the solder in the solder paste contains nickel-based amorphous powder and titanium-containing powder. The titanium-containing powder can react with boron nitride ceramics during the brazing heat treatment to generate titanium nitride and titanium boride, thereby achieving the reaction and effective bonding between boron nitride ceramics and solder.
[0039] It should be noted that, in order to achieve an interfacial reaction between the solder and the boron nitride ceramic without affecting the cladding connection between the solder and the nickel-based superalloy, the present invention requires limiting the solder ratio.
[0040] Specifically, the mass ratio of the nickel-based amorphous powder to the titanium hydride powder is 7:3 to 9:1, such as 7:3, 7.5:2.5, 8:2, 8.5:1.5, and 9:1. Too little titanium powder content will cause the nickel-based amorphous solder to react with the titanium powder without reacting with the titanium layer, resulting in a reduced bonding strength between the titanium layer and the solder layer. Too much titanium powder content will lead to a higher melting point of the solder and an excessive amount of brittle phase compounds in the joint, reducing the joint strength. Within the solder content range specified in this invention, a joint with better welding quality can be obtained.
[0041] It is worth noting that this invention regulates the ratio of nickel-based amorphous powder to titanium-containing powder in the brazing filler metal. On the one hand, it controls the melting point of the filler metal to reach the temperature at which boron nitride ceramic can react with titanium, thus achieving an interfacial reaction between the filler metal and boron nitride. On the other hand, it controls the melting point range of the filler metal so that during the brazing process, boron nitride ceramic reacts with titanium to generate substances (TiN, TiB2) and structures that are beneficial to enhancing the interfacial bonding strength between ceramic and filler metal, preventing the formation of a porous interfacial layer. Furthermore, it also avoids the degradation of the performance of nickel-based high-temperature alloys caused by excessively high brazing temperatures.
[0042] It should be noted that, by weight percentage, the nickel-based amorphous powder contains 2.75%-3.5% B, 4%-5% Si, 6.0%-8.0% Cr, 2.5%-3.5% Fe, ≤0.06% carbon, and the balance being Ni. It should also be noted that, in order to prevent oxidation of the brazing filler metal during ball milling and subsequent heat treatment, and to ensure the purity of the filler metal and the quality of subsequent brazing connections, this invention requires limiting the chemical composition of the titanium-containing powder in the brazing filler metal.
[0043] Specifically, the titanium-containing powder is titanium hydride powder. Compared with pure Ti, the titanium hydride in the composite brazing filler metal of this invention has higher chemical stability. It is not easily oxidized during the ball milling and mixing process with Ni-based amorphous powder and during the subsequent heat treatment brazing process. Moreover, it can dehydrogenate to form titanium at temperatures above 400°C, efficiently participating in the interfacial reaction of brazing and fully exerting its regulatory role, which is more conducive to the effective and high-strength connection between BN ceramics and Ni-based superalloys.
[0044] It should be noted that, in order to ensure that the components of the composite brazing filler metal are fully and uniformly mixed, the present invention uses ball milling to mix the nickel-based amorphous powder and the titanium hydride powder. The specific steps include: S1: Weighing the nickel-based amorphous powder and the titanium-containing powder in proportion, wherein the mass ratio of the nickel-based amorphous powder to the titanium-containing powder is 7:3 to 9:1; S2: Vacuum ball milling mixing.
[0045] Specifically, in step S1, the mass ratio of the nickel-based amorphous powder to the titanium-containing powder is 7.5:2.5 to 8.5:1.5.
[0046] Specifically, in step S2, the conditions for vacuum ball milling include: evacuation, nitrogen injection for protection, under a nitrogen atmosphere of 0.1-0.3 MPa, a ball-to-material ratio of 10:1-20:1, a rotation speed of 80-120 rpm, and a ball milling time of 10-30 min.
[0047] According to some preferred embodiments of the present invention, the ball-to-powder ratio can be any value in the range of 10:1 to 20:1, such as 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1. If the ball-to-powder ratio is too low, it is easy to cause uneven mixing; if the ball-to-powder ratio is too high, it will cause excessive grinding energy, smaller powder size, and poor mixing.
[0048] It should be noted that, in order to prevent the oxidation of the brazing filler metal during the ball milling process, nitrogen gas needs to be injected into the vacuum-sealed ball mill jar for protection, so that the raw materials are mixed in a nitrogen atmosphere of 0.1-0.3 MPa.
[0049] According to some preferred embodiments of the present invention, the nitrogen pressure in the ball mill can be any value in the range of 0.1-0.3 MPa, such as 0.1 MPa, 0.15 MPa, 0.2 MPa, 0.25 MPa, or 0.3 MPa. If the pressure is too low, it is easy to cause the raw material to oxidize in the ball mill. If the pressure is too high, it will cause the powder to spray out due to pressure relief during the opening process.
[0050] According to some preferred embodiments of the present invention, the ball milling speed can be any value within the range of 80-120 rpm, such as 80 rpm, 85 rpm, 90 rpm, 95 rpm, 100 rpm, 105 rpm, 110 rpm, 115 rpm, and 120 rpm. If the speed is too high, it is easy to cause the raw materials to separate and the mixing to be uneven; if the speed is too low, the mixing efficiency is low and the ball milling time is long.
[0051] According to some preferred embodiments of the present invention, the ball milling time can be any value in the range of 10-30 min, such as 10 min, 15 min, 20 min, 25 min, or 30 min. If the time is too short, the mixing will be uneven; if the time is too long, the raw materials will easily separate and the mixing will be uneven.
[0052] It should be noted that, in order to improve the wettability of the composite solder with the surface to be soldered, and to enable the solder paste to form and remain stably between the surfaces to be soldered, the present invention needs to limit the ratio between the nickel-based composite solder, the paste carrier, and the solvent.
[0053] Specifically, the solder paste further includes a paste carrier and an organic solvent, wherein the mass ratio of the solder to the paste carrier and the organic solvent is 1:(1-3):(5-8). The paste carrier is rosin, acrylic resin, etc., combined with at least one organic solvent such as acetone or isopropanol.
[0054] It should be noted that, in order to ensure the brazing connection strength while avoiding excessive content of brittle phase in the intermediate layer, which would affect the mechanical strength of the joint, the present invention needs to control the amount of solder paste used.
[0055] Specifically, the thickness of the solder paste is 50-200mm. If the solder paste is too thin, it can easily affect the interfacial bonding strength between the solder and the titanium layer and nickel-based superalloy; if it is too thick, the solder will have an erosion effect on the base material, which defeats the purpose of brazing.
[0056] It should be noted that, in order to enable the chemically inert boron nitride ceramic to achieve effective bonding with nickel-based superalloys through interfacial reaction with the solder, the present invention requires modification treatment of the test surface of the boron nitride ceramic.
[0057] Specifically, in step (1), a Ti film is deposited on the surface of the boron nitride ceramic.
[0058] It is noteworthy that in the subsequent vacuum heat treatment of joining BN ceramic and Ni-based superalloy using nickel-based composite solder, the titanium film exhibits the following characteristics: On one hand, the titanium layer in contact with the BN ceramic reacts with BN to form a TiN thin layer. TiN has excellent wetting and pinning effects on boron nitride, which improves the bonding strength between the titanium layer and the BN ceramic. On the other hand, the titanium layer away from the BN ceramic reacts with the nickel-based composite solder to form intermetallic compounds such as TiNi. Simultaneously, the nickel-based composite solder and the Ni-based superalloy undergo high-temperature solid solution treatment. The titanium nitride layer, the titanium layer, and the reacted intermetallic compound layer provide a gradient material with different coefficients of thermal expansion, significantly reducing the interfacial thermal stress generated during the heat treatment connection of ceramic and metal, thereby achieving an effective connection between the two.
[0059] It should be noted that, in order to facilitate the effective (crack-free interface) and high-strength connection between BN ceramic and Ni-based high-temperature metal through the interfacial reaction between the titanium layer and the ceramic surface, and the interfacial reaction between the titanium layer and the composite solder during subsequent heat treatment, this invention needs to limit the thickness of the titanium film deposited on the BN ceramic surface.
[0060] Specifically, the thickness of the titanium film is 1-4 μm.
[0061] According to some preferred embodiments of the present invention, the thickness of the titanium film can be any value within the range of 1-4 μm, such as 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, and 4 μm. If the titanium film is too thin, it will be completely reacted by the BN ceramic and the brazing filler metal during the subsequent heat treatment of brazing, making it impossible to form an intermediate layer with a sufficiently gradient structure between the ceramic to be welded and the nickel-based superalloy, leading to joint failure due to internal stress. If the titanium film is too thick, the joint will also fail due to the poor strength of the titanium film itself. Within the thickness range defined by the present invention, a higher connection strength can be obtained.
[0062] It should be noted that, in order to improve the adhesion and density of the titanium film on the ceramic surface and to precisely control the film thickness at the micro-nano level, the present invention uses magnetron sputtering to deposit a titanium film on the surface of the boron nitride ceramic to be welded after cleaning.
[0063] More specifically, the present invention employs magnetron sputtering to deposit a titanium film on the cleaned boron nitride ceramic surface to be soldered, under the following conditions: a vacuum degree of 5 × 10⁻⁶. -5 Pa-7×10 -5 The argon pressure range is 0.5Pa-2Pa, the target distance is 100-190mm, the DC power supply power is 180W-220W, and the time is 2-8h.
[0064] It should be noted that, in order to prevent the titanium film from being oxidized during the preparation process, the present invention needs to limit the base vacuum level of magnetron sputtering; appropriate argon pressure, target distance, and power supply can work together to ensure the adhesion, uniformity, and density of the titanium film; the length of sputtering time determines the thickness of the titanium film.
[0065] According to some preferred embodiments of the present invention, the vacuum degree of magnetron sputtering of the present invention can be 5 × 10⁻⁶. -5 Pa-7×10 -5 Any value within the Pa range, such as 5 × 10 -5 Pa, 5.5 × 10 -5 Pa, 6×10 -5 Pa, 6.5 × 10 -5 Pa, 7×10 -5 Pa.
[0066] According to some preferred embodiments of the present invention, the argon gas pressure of the magnetron sputtering of the present invention can be any value in the range of 0.5Pa-2Pa, such as 0.5Pa, 0.8Pa, 1Pa, 1.2Pa, 1.5Pa, 1.7Pa, 2Pa; the target distance of the magnetron sputtering of the present invention can be any value in the range of 100-190mm, such as 100mm, 110mm, 120mm, 130mm, 140mm, 150mm, 160mm, 170mm, 180mm, 190mm; and the DC power supply power of the magnetron sputtering of the present invention can be any value in the range of 180W-220W, such as 180W, 190W, 200W, 210W, 220W.
[0067] It is worth noting that this invention uses magnetron sputtering to deposit a titanium film on the surface of BN ceramics. The titanium film formed by bombardment with high-energy Ar particles in a vacuum environment has strong adhesion and high density on the ceramic surface. The film thickness can be precisely controlled at the micro-nano level, such as 1-4 μm. This is beneficial for the subsequent vacuum brazing process, through the interfacial reaction between the titanium layer and the ceramic surface, as well as the interfacial reaction between the titanium layer and the composite brazing filler metal, to achieve an effective and high-strength (room temperature shear strength up to 3.48 MPa) connection between BN ceramics and Ni-based high-temperature metals.
[0068] It should be noted that, in order to ensure the bonding quality of the brazing interface while fixing the relative positions between the layers to be welded, the present invention requires the use of a mold to press the boron nitride ceramic and the nickel-based high-temperature alloy, which are placed between the surfaces to be welded with composite brazing filler metal, and to limit the pressing pressure.
[0069] Specifically, in step (2), the pressure of the mold clamping is 0.2-1 MPa. If the pressure is too high, the solder paste will be squeezed out between the surfaces to be soldered. If the pressure is too low, the gases generated during the heat treatment process, including the gases generated by the thermal decomposition of the paste carrier and the hydrogen generated by the heating of titanium hydride, will cause residual bubbles in the intermediate layer connecting the BN ceramic and the Ni-based superalloy, affecting the bonding strength of the joint interface.
[0070] According to some preferred embodiments of the present invention, the pressure of the mold during clamping can be any value in the range of 0.2-1MPa, such as 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa, 0.6MPa, 0.7MPa, 0.8MPa, 0.9MPa, or 1MPa.
[0071] It should be noted that, in order to improve the interfacial bonding strength between the titanium layer and boron nitride, as well as the reaction between the titanium layer and the brazing filler metal, and to ensure that the physicochemical properties of the nickel-based superalloy are not affected by high temperature, and to maintain the intrinsic properties of the alloy to the greatest extent, this invention needs to limit the brazing heat treatment process steps and process parameters.
[0072] Specifically, in step (3), the vacuum degree of the brazing heat treatment is 3×10⁻⁶. -3 Pa ~ 5 × 10 -3 Pa, the vacuum environment of heat treatment can prevent metallic Ti from being oxidized into TiO2, which would affect the solder reaction.
[0073] According to some preferred embodiments of the present invention, the vacuum degree of the heat treatment of the present invention can be any value in the range of 3×10-3 Pa to 5×10-3 Pa, such as 3×10-3 Pa, 3.5×10-3 Pa, 4×10-3 Pa, 4.5×10-3 Pa, 5×10-3 Pa.
[0074] Specifically, in step (3), the brazing heat treatment is carried out at a temperature of 1000℃-1100℃ for 5min-25min. By controlling the temperature and time of the heat treatment, not only can the solid-solid reaction between the titanium layer and boron nitride be promoted to generate a TiN thin layer with a stronger bond to the substrate, but the physicochemical properties of nickel-based high-temperature alloys can also be avoided from being affected by high temperature.
[0075] According to some preferred embodiments of the present invention, the heat treatment temperature of the present invention is any value in the range of 1000℃-1100℃, such as 1000℃, 1020℃, 1050℃, 1080℃, and 1100℃.
[0076] In some preferred embodiments of the present invention, the heat treatment time is any value within the range of 5 min to 25 min, such as 5 min, 7 min, 10 min, 12 min, 15 min, 18 min, 20 min, 23 min, and 25 min.
[0077] It should be noted that, in order to promote the discharge of gas during the heat treatment heating process and improve the interface bonding quality, the present invention needs to limit the rate of the heating process.
[0078] Specifically, in step (3), the brazing heat treatment also includes a heating stage, the heating rate of which is 8℃ / min-12℃ / min. If the heating rate is too low, it will affect the heat treatment efficiency. If the heating rate is too high, it will easily lead to the gas generated by the thermal decomposition of the paste carrier (300-400℃) and the hydrogen volatilized from the decomposition of titanium hydride not being able to be discharged in time. This will result in bubbles in the intermediate layer formed by the interface reaction between the brazing filler and the titanium layer and the alloy surface, affecting the strength. In addition, a suitable heating rate can also allow the titanium hydride in the composite brazing filler to completely volatilize the hydrogen before the nickel-based amorphous brazing filler melts and is brazed, so as to obtain pure Ti that truly plays a role in brazing, and timely and effectively prevent excessive reaction between the nickel-based amorphous alloy and the Ti layer.
[0079] It should be noted that, in order to avoid excessive thermal stress concentration due to the difference in thermal expansion coefficients between different material layers during the heat treatment cooling process, which could cause interface cracks and lead to joint failure, this invention needs to limit the cooling method after brazing heat treatment.
[0080] Specifically, in step (3), the cooling process includes: first reducing the temperature to 400-500℃ at a rate of 2-6℃ / min, and then furnace cooling to room temperature. Due to the high heat treatment temperature, during the cooling and solidification process in the high-temperature section (500-1100℃), it is necessary to continue heating to control the slow cooling of the joint and avoid thermal stress cracking at the brazing filler metal reaction interface; when the temperature reaches the low-temperature section, the joint can be slowly cooled down with the furnace.
[0081] It is worth noting that, by adjusting the brazing heat treatment process parameters, including the heating rate, heating temperature, holding time, and cooling method, this invention not only promotes the solid-solid reaction between the titanium layer and boron nitride to generate a TiN and TiB2 reaction thin layer that is firmly bonded to the matrix, but also allows the titanium hydride in the composite brazing filler metal to completely evaporate hydrogen before the nickel-based amorphous brazing filler metal melts and is brazed, thus obtaining pure Ti that truly plays a role in brazing. In addition, this invention greatly reduces the thermal stress generated during the cooling process of the brazed joint by slow cooling, avoiding cracks at the interface between BN ceramic and Ni-based superalloy that could lead to joint failure, thereby achieving an effective and high-strength connection between BN ceramic and Ni-based superalloy.
[0082] It is worth noting that the upper limit of the vacuum brazing temperature is 1100℃, which will not affect the physicochemical properties of the Ni-based superalloy. This preserves the performance of the Ni-based superalloy to the greatest extent, allowing the BN ceramics effectively connected to it to truly play the role of a high-temperature thermal structural material for thermal management. This is conducive to the promotion and application of BN ceramics in aerospace, nuclear energy and other fields.
[0083] According to some preferred embodiments of the present invention, a brazing heat treatment method for boron nitride ceramics and nickel-based superalloys is described in the following process flow: Figure 1 As shown, the method includes:
[0084] ① Grind and clean the surfaces of boron nitride ceramic and nickel-based superalloy to be welded, respectively;
[0085] ② Deposit a titanium film on the surface of the boron nitride ceramic to be welded after cleaning;
[0086] ③Preparation of nickel-based composite solder;
[0087] ④ Place the nickel-based composite brazing filler metal between the boron nitride ceramic and the nickel-based high-temperature alloy surfaces to be welded, and press it down with the mold;
[0088] ⑤ Heat treatment to achieve brazing connection between boron nitride ceramics and nickel-based high-temperature alloys.
[0089] It should be noted that in order to improve the adhesion strength of the titanium film on the BN ceramic surface and the wettability of the solder on the Ni-based superalloy surface, it is necessary to remove contaminants from both solder surfaces. The contaminants are one or more of the following: oxide film, adsorbed water film, organic oil, and metal debris.
[0090] According to some preferred embodiments of the present invention, the surfaces of boron nitride ceramic and nickel-based high-temperature alloy to be welded are polished with 1000-grit sandpaper and then ultrasonically cleaned with acetone for 10 minutes.
[0091] On the other hand, embodiments of the present invention also provide a connecting joint between boron nitride ceramic and nickel-based high-temperature alloy, wherein the connecting joint is prepared by the method described above, and the shear stress of the connecting joint is 1-4 MPa at 25°C.
[0092] According to some preferred embodiments of the present invention, the connection joint between boron nitride ceramic and nickel-based superalloy obtained using the solder paste described in the present invention, such as... Figure 4 As shown, it includes boron nitride ceramic, an intermediate layer and a nickel-based superalloy connected in sequence; wherein, in the direction from the boron nitride ceramic to the nickel-based superalloy, the intermediate layer includes a Ti layer-boron nitride reaction layer, a Ti layer, a solder-Ti layer reaction layer, a solder layer and a nickel-based superalloy-solder reaction layer.
[0093] Compared with existing technologies, this invention proposes for the first time a joint connecting boron nitride ceramics and nickel-based superalloys. The joint contains a solder-boron nitride reaction layer formed by the reaction of nickel-containing solder and boron nitride, which enables effective bonding of the chemically inert boron nitride ceramics and nickel-based superalloys at the microscopic level. The TiN and TiB2 contained in the solder-boron nitride reaction layer can improve the interfacial wetting between the BN ceramics and titanium or titanium alloys, provide chemical bonding between the BN ceramics and the solder reaction layer, and act as a reinforcing phase to enhance interfacial bonding.
[0094] It should be noted that, taking into account the thermal stability and thermal conductivity of boron nitride, as well as processing feasibility and economic cost, this invention needs to limit the type of boron nitride.
[0095] Specifically, the boron nitride ceramic described in this invention is a hexagonal boron nitride ceramic.
[0096] It should be noted that, in order to adapt to the application of boron nitride ceramics in the thermal management of high-temperature thermal structural materials, the present invention needs to define the structural shape of boron nitride ceramics.
[0097] Specifically, the boron nitride ceramic of the present invention is in the form of sheets or blocks.
[0098] It should be noted that, in order to enhance the effective connection between the boron nitride ceramic and the solder, the present invention designs a multi-layer structure for the solder-boron nitride reaction layer between the two.
[0099] Specifically, the solder-boron nitride reaction layer includes a boron nitride-Ti layer reaction layer, a Ti layer, and a solder-Ti layer reaction layer.
[0100] It should be noted that, in order to improve the effective connection between the boron nitride ceramic and the Ti layer, and at the same time avoid interface embrittlement, the present invention needs to adjust the composition and thickness of the boron nitride-Ti layer reaction layer obtained by the reaction of the two.
[0101] Specifically, the boron nitride-Ti layer reaction layer contains TiN and TiB2. During the preparation process, nitrogen diffuses much faster than boron, making it easier for nitrogen to react with titanium from the boron nitride ceramic side to form TiN. Boron, on the other hand, reacts relatively slowly and accumulates on the side closer to BN to form TiB2.
[0102] It should be noted that TiN has a face-centered cubic structure, high hardness, high chemical stability, excellent metallic conductivity, and good lattice matching with Ti, effectively blocking the further diffusion of B atoms into the Ti matrix and inhibiting the excessive growth of the reaction layer; its coefficient of thermal expansion is between that of Ti and TiB2 / BN, which helps to alleviate thermal mismatch stress; compared with TiB2, TiN has a certain degree of toughness and can prevent crack propagation.
[0103] It should be noted that TiB2 (titanium diboride) has a hexagonal structure, exhibiting extremely high hardness, high melting point, high wear resistance, excellent metallic electrical and thermal conductivity, and is a major contributor to interfacial strength. It has a similar crystal structure to BN (both are hexagonal) and exhibits crystallographic continuity with BN. It can form strong chemical bonds with BN, acting as an "anchor point" to BN ceramics, effectively transferring loads from the relatively soft titanium matrix to the hard BN ceramics.
[0104] Specifically, the thickness of the boron nitride-Ti reaction layer is 0.1-0.5 μm. If the thickness is too large, it will cause it to detach from the boron nitride substrate; if the thickness is too small, it will be impossible to form a good and stable connection. The thickness can be 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, or 0.5 μm.
[0105] It should be noted that, in order to improve the effective connection between boron nitride ceramic and solder, while alleviating the concentration of interfacial thermal stress and preventing interfacial embrittlement, the present invention needs to limit the thickness of the titanium layer.
[0106] More specifically, the thickness of the titanium layer is 1-4 μm. If the titanium layer is too thick, it will cause delamination and fracture of the titanium layer itself; if the titanium layer is too thin, it will lose its thermal stress relief effect. The thickness can be 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, or 4 μm.
[0107] It should be noted that, in order to ensure the connection strength between the Ti layer and the solder layer while avoiding interface embrittlement, the present invention needs to limit the thickness of the solder-Ti layer reaction layer.
[0108] Specifically, the thickness of the solder-Ti reaction layer is 0.1-0.5 μm. If the reaction layer thickness is too large, it will lead to interface brittleness and lower joint strength; if the reaction layer thickness is too small, it will prevent the formation of an effective connection. The thickness can be 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, or 0.5 μm.
[0109] It should be noted that, in order to obtain the weld joint with the best performance, the present invention needs to limit the thickness of the brazing filler metal reaction layer.
[0110] Specifically, the thickness of the solder reaction layer is 20-200 μm. If the solder reaction layer is too thick, the solder reaction will be insufficient, resulting in excessive interfacial compounds and reduced joint strength; if the solder reaction layer is too thin, an effective connection cannot be achieved. The thickness can be 20 μm, 40 μm, 80 μm, 100 μm, 120 μm, 140 μm, 160 μm, 180 μm, or 200 μm.
[0111] It should be noted that, in order to achieve better connection, the present invention needs to limit the thickness of the metal cladding layer, which serves as the brazing filler metal-nickel-based superalloy reaction layer.
[0112] Specifically, the thickness of the metal cladding layer is 5–25 μm. If the solder-nickel-based superalloy reaction layer is too large, it will cause corrosion of the base material and affect the performance of the base material; if the solder-nickel-based superalloy reaction layer is too small, it will result in low bonding strength. The thickness can be 5 μm, 10 μm, 15 μm, 20 μm, or 25 μm.
[0113] It should be noted that the boron nitride ceramic and nickel-based superalloy connection joint provided by the present invention not only achieves an effective connection between the boron nitride ceramic and the nickel-based superalloy, but also achieves a high-strength connection through structural optimization.
[0114] Specifically, the shear strength of the connecting joint is 0.4-4 MPa.
[0115] The connection joint between boron nitride ceramics and nickel-based superalloys prepared by the brazing heat treatment method of this invention not only enables effective (crack-free interfacial bonding intermediate layer) and high bonding strength connection between BN ceramics and nickel-based superalloys, but also preserves the intrinsic properties of Ni-based superalloys to the greatest extent. This allows the effectively connected BN ceramics to truly function as a high-temperature thermal structural material for thermal management, which is conducive to the promotion and application of BN ceramics in aerospace, nuclear energy and other fields.
[0116] The technical solution of the present invention will be further explained and illustrated below through examples and comparative examples.
[0117] The Ni-based superalloy used in the examples and comparative examples is GH4169, which is mainly composed of Ni, Cr, Fe and small amounts of Mo and Nb, and is widely used in aircraft structural components.
[0118] The BN ceramics used in the examples and comparative examples are hexagonal boron nitride ceramics (h-BN).
[0119] Example 1
[0120] A brazing heat treatment method for boron nitride ceramics and nickel-based superalloys, specifically comprising:
[0121] ① After polishing the surfaces to be welded of GH4169 nickel-based high-temperature alloy and h-BN ceramic with 1000 grit sandpaper, they were ultrasonically cleaned with acetone for 10 minutes.
[0122] ② The cleaned h-BN workpiece is placed into a magnetron sputtering apparatus for magnetron sputtering titanium film deposition, under the following conditions: background vacuum degree 5×10 -5 Pa, argon pressure 1 Pa, DC power supply power 200 W, coating time 6 h, a 3 μm thick titanium film was obtained on the h-BN ceramic surface.
[0123] ③ Place nickel-based amorphous brazing filler powder (200 mesh) and titanium hydride powder (400 mesh) in a vacuum ball mill jar with a mass ratio of 9:1, evacuate the jar, inject 0.2 MPa nitrogen for protection, the ball-to-filler ratio is 15:1, the horizontal ball mill speed is 120 r / min, grind for 10 min to obtain composite brazing filler, and mix with solvent and paste carrier to obtain composite brazing filler paste, wherein the mass ratio of composite brazing filler to solvent and paste carrier is 1:3:5;
[0124] ④ Place the composite solder paste obtained in step (3) between GH4169 and the coated hexagonal boron nitride ceramic surface to be soldered, with a thickness of 100mm, and press it with a graphite mold with a pressure of about 0.4MPa.
[0125] ⑤ Place it in a vacuum furnace and wait until the vacuum level of the furnace reaches 4×10⁻⁶. -3At Pa, the heating process involves raising the temperature to 1050℃ at a rate of 10℃ / min and holding it for 15min; then lowering the temperature to 400℃ at a rate of 5℃ / min, shutting off the heating, and allowing the furnace to cool to room temperature, thus obtaining the connection joint between h-BN ceramic and GH4169 nickel-based superalloy. The actual connection joint is shown in the image. Figure 2 As shown, the SEM image of the connector is as follows: Figure 3 As shown, from Figure 3 It can be seen that nickel-based superalloys and BN ceramics can achieve a tight bond at the microscopic level; the test results show that the shear strength of the joint at room temperature reaches 3.48 MPa.
[0126] Example 2
[0127] The same method as in Example 1 was used for the brazing heat treatment of boron nitride ceramic and nickel-based superalloy. The difference was that in step ②, the coating time was 4 hours, and a 2 μm thick titanium film was obtained on the surface of the h-BN ceramic. Finally, a joint between the h-BN ceramic and the GH4169 nickel-based superalloy was obtained. The shear strength of the joint at room temperature reached 3.24 MPa after testing.
[0128] Example 3
[0129] The same method as in Example 1 was used for the brazing heat treatment of boron nitride ceramic and nickel-based superalloy. The difference was that in step ②, the coating time was 2 hours, and a 1 μm thick titanium film was obtained on the surface of the h-BN ceramic. Finally, a joint between the h-BN ceramic and the GH4169 nickel-based superalloy was obtained. The shear strength of the joint at room temperature reached 2.99 MPa.
[0130] Example 4
[0131] The same method as in Example 1 was used for brazing heat treatment of boron nitride ceramic and nickel-based superalloy. The difference was that in step ③, the mass ratio of nickel-based amorphous brazing filler powder (200 mesh) to titanium hydride powder (400 mesh) was 8:2, and a joint between h-BN ceramic and GH4169 nickel-based superalloy was finally obtained. The shear strength of the joint at room temperature reached 1.50 MPa.
[0132] Example 5
[0133] The same method as in Example 4 was used for the brazing heat treatment of boron nitride ceramic and nickel-based superalloy. The difference was that in step ②, the coating time was 4 hours, and a 2 μm thick titanium film was obtained on the surface of the h-BN ceramic. Finally, a joint between the h-BN ceramic and the GH4169 nickel-based superalloy was obtained. The shear strength of the joint at room temperature reached 3.39 MPa.
[0134] Example 6
[0135] The same method as in Example 4 was used for the brazing heat treatment of boron nitride ceramic and nickel-based superalloy. The difference was that in step ②, the coating time was 2 hours, and a 1 μm thick titanium film was obtained on the surface of the h-BN ceramic. Finally, a joint between the h-BN ceramic and the GH4169 nickel-based superalloy was obtained. The shear strength of the joint at room temperature reached 1.85 MPa.
[0136] Example 7
[0137] The same method as in Example 3 was used for brazing heat treatment of boron nitride ceramic and nickel-based superalloy. The difference was that in step ③, the mass ratio of nickel-based amorphous brazing filler powder (200 mesh) to titanium hydride powder (400 mesh) was 7:3, and a joint between h-BN ceramic and GH4169 nickel-based superalloy was finally obtained. The shear strength of the joint at room temperature reached 1.24 MPa.
[0138] Example 8
[0139] The same method as in Example 1 was used for the brazing heat treatment of boron nitride ceramic and nickel-based superalloy. The difference was that in step ④, the thickness of the solder paste placed between GH4169 and the coated hexagonal boron nitride ceramic to be welded was 150 mm, and the final connection joint between h-BN ceramic and GH4169 nickel-based superalloy was obtained. The shear strength of the connection joint at room temperature reached 3.32 MPa after testing.
[0140] Example 9
[0141] The same brazing heat treatment of boron nitride ceramic and nickel-based superalloy was performed as in Example 1, except that step ② was not included, i.e., no titanium layer was prepared on the surface of BN ceramic in Comparative Example 1. The final result was a joint between h-BN ceramic and GH4169 nickel-based superalloy. The shear strength of the joint at room temperature was tested to be 0.4 MPa.
[0142] Example 10
[0143] The same method as in Example 1 was used for the brazing heat treatment of boron nitride ceramic and nickel-based superalloy. The difference was that in step ②, the coating time was 1 hour, and a 0.5 μm thick titanium film was obtained on the surface of the h-BN ceramic, finally obtaining the connection joint between h-BN ceramic and GH4169 nickel-based superalloy. The connection joint obtained by this method does not have a titanium layer, and the shear strength of the connection joint at room temperature is 0.52 MPa.
[0144] Example 11
[0145] The same method as in Example 1 was used for the brazing heat treatment of boron nitride ceramic and nickel-based superalloy. The difference was that in step ⑤, the temperature was increased to 1000°C, and a joint between h-BN ceramic and GH4169 nickel-based superalloy was finally obtained. The shear strength of the joint at room temperature was tested to be 2.95 MPa.
[0146] Example 12
[0147] The same brazing heat treatment of boron nitride ceramic and nickel-based superalloy was performed as in Example 1. The difference was that in step ⑤, the temperature was increased to 1100°C, and a joint between h-BN ceramic and GH4169 nickel-based superalloy was finally obtained. The shear strength of the joint at room temperature was tested to be 3.26 MPa.
[0148] Example 13
[0149] The same method as in Example 1 was used for the brazing heat treatment of boron nitride ceramic and nickel-based superalloy. The difference was that in step ⑤, the holding time was 25 min, and a joint between h-BN ceramic and GH4169 nickel-based superalloy was finally obtained. The shear strength of the joint at room temperature was tested to be 3.15 MPa.
[0150] Comparative Example 1
[0151] The same method as in Example 1 was used for the brazing heat treatment of boron nitride ceramic and nickel-based superalloy. The difference was that in step ②, the coating time was 8 hours, and a 4 μm thick titanium film was obtained on the surface of the h-BN ceramic. The connection joint could not be obtained by using the method of Comparative Example 1 because the titanium film was too thick, which caused the titanium layer to crack during the heat treatment process.
[0152] Comparative Example 2
[0153] The same method as in Example 1 was used for the brazing heat treatment of boron nitride ceramic and nickel-based high-temperature alloy. The difference was that in step ④, the thickness of the solder paste placed between GH4169 and the coated hexagonal boron nitride ceramic to be soldered was 300 mm. The resulting joint did not form an effective connection, and the macroscopic fracture location was located in the middle of the solder.
[0154] Comparative Example 3
[0155] The same method as in Example 1 was used for the brazing heat treatment of boron nitride ceramic and nickel-based superalloy. The difference was that in step ⑤, the temperature was increased to 1150°C, and a joint between h-BN ceramic and GH4169 nickel-based superalloy was finally obtained. Upon inspection, the GH4169 nickel-based superalloy in the joint showed obvious grain coarsening and softening.
[0156] The structural composition, dimensional parameters, and connection performance characterization of the connectors obtained using the above embodiments and comparative examples are shown in Table 1:
[0157] Table 1. Structural composition, dimensional parameters, and performance characteristics of the connection joints in the embodiments and comparative examples.
[0158]
[0159]
[0160] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. A brazing heat treatment method for boron nitride ceramics and nickel-based superalloys, characterized in that, The method includes: (1) Placing the solder paste between the boron nitride ceramic and the nickel-based superalloy surfaces to be soldered, wherein the solder paste comprises nickel-based amorphous powder and titanium hydride powder, wherein the mass ratio of the nickel-based amorphous powder to the titanium hydride powder is 7:3 to 9:1, and the nickel-based amorphous powder comprises, by weight percentage, 2.75%-3.5% B, 4%-5% Si, 6.0%-8.0% Cr, 2.5%-3.5% Fe, ≤0.06% carbon, and the balance being Ni; (2) Mold clamping; (3) The brazing heat treatment is carried out at a temperature of 1000℃-1100℃ for 5min-25min to achieve the brazing connection between the boron nitride ceramic and the nickel-based high-temperature alloy. The brazing heat treatment also includes a heating stage and a cooling stage. The heating stage has a rate of 8℃ / min-12℃ / min. The cooling stage specifically includes: first cooling to 400-500℃ at a rate of 2-6℃ / min, and then furnace cooling to room temperature.
2. The method according to claim 1, characterized in that, The mass ratio of the nickel-based amorphous powder to the titanium hydride powder is 7.5:2.5 to 8.5:1.
5.
3. The method according to claim 2, characterized in that, The thickness of the solder paste is 50-200 mm.
4. The method according to claim 1, characterized in that, In step (2), the pressure of the mold clamping is 0.2-1 MPa.
5. The method according to claim 1, characterized in that, In step (3), the vacuum degree of the brazing heat treatment is 3×10⁻⁶. -3 Pa~5×10 -3 Pa.
6. A connecting joint between boron nitride ceramic and nickel-based superalloy, characterized in that, The connecting joint is made by the method according to any one of claims 1-5, wherein the shear stress of the connecting joint is 0.4-4 MPa at 25°C.
Citation Information
Patent Citations
Tantalum-containing high-temperature brazing material for brazing ceramic and metal and brazing assistance method of tantalum-containing high-temperature brazing material
CN105458551A
Brazing method for connecting ceramic and metal material
CN110436952A
